A girl with Henoch Schönlein purpura associated with acute rheumatic fever and review of literature - Ebru Aypar; Duygu Demirtaş; Hayrettin Hakan Aykan; Fehime Kara-Eroğlu; Ali Düzova (The Turkish Journal of Pediatrics)
Henoch Schönlein purpura (HSP) with acute rheumatic fever (ARF) is a rare entity and only few cases have been reported so far. In all previously reported cases with HSP and ARF, patients initially presented with purpuric rash, arthralgia/arthritis, or abdominal pain and later diagnosed as ARF. We report an 11-year-old girl with features of both ARF and HSP. She initially presented with arthralgia and murmur. Echocardiography showed mild to moderate mitral regurgitation. Later, the clinical course was complicated by purpuric rash and abdominal pain. She was treated conservatively with IM penicillin, acetylsalicylic acid and oral prednisolone. Our patient is the first patient with HSP and ARF who initially presented with features of ARF. A review of literature revealed a limited number of cases of HSP associated with ARF (14 cases including the present case); and that the response to treatment in cases suffering from ARF associated with HSP was good; but one should also be aware of serious cardiac complications in HSP patients which may be fatal.